Oxidative Status and Histological Evaluation of Wild Boars' Tissues Positive for Zearalenone Contamination in the Campania Region, Southern Italy - Sara Damiano; Consiglia Longobardi; Gianmarco Ferrara; Nadia Piscopo; Lorenzo Riccio; Valeria Russo; Valentina Meucci; Lucia De Marchi; Luigi Esposito; Salvatore Florio; Roberto Ciarcia (MDPI AG, 2023)
Zearalenone (ZEN) is a mycotoxin produced by fungi belonging to the genera Fusarium spp. and commonly found in feed and food. It is frequently related to reproductive disorders in farm animals and, occasionally, to hyperestrogenic syndromes in humans. Nowadays, knowledge about ZEN effects on wild boars (Sus scrofa) is extremely scarce, despite the fact that they represent one of the most hunted game species in Italy. The aim of this study was to investigate how ZEN affects the liver, kidney, and muscle oxidative status and morphology of wild boars hunted in various locations throughout the province of Avellino, Campania Region, Southern Italy, during the 2021-2022 hunting season. Superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities, as well as the malondialdehyde (MDA) levels, were assessed by colorimetric assays; tissue morphology was evaluated by hematoxylin-eosin and Masson's stains. Our data showed that ZEN contamination might result in oxidative stress (OS) and some histopathological alterations in wild boars' livers and kidneys rather than in muscles, emphasizing the importance of developing a wildlife monitoring and management strategy for dealing not only with the problem of ZEN but the surveillance of mycotoxins in general.